Industry Practices, Processes and Techniques Adopted in Education Supporting Innovative Teaching and Learning Practice - MacCallum, Kathryn; Parsons, David (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides a single source of reference for educators interested in understanding how industry-based ideas have been adapted into different educational contexts, and supports their utilisation in practice. The link between industry-based ideas and their application in education has enabled educators to develop engaging, collaborative, and creative learning environments, as well as better preparing their students for an increasingly complex and dynamic global environment. This book includes contributions from educators, researchers, and practitioners, who have integrated industry-based ideas into their teaching, and explores how these concepts and practices support the creation of effective learning environments. Through these diverse, international contributions, this book enables wider engagement with, and critical analysis of, the application of industry practices, processes and techniques in the development of collaborative and creative learning environments.
Keywords: Teaching; Education-Curricula.; Education, Higher; Educational technology; Professional education; Vocational education; Didactics and Teaching Methodology; Curriculum Studies; Higher Education; Digital Education and Educational Technology; Professional and Vocational Education